American Civil Liberties Union of Northern California Honors Howard Watkins with Lola Hanzel Courageous Advocacy Award - Watkins, Howard::::::::: (1987)
Aileen Hernandez, Hon. Cruz Reynoso, ? And Fred Korematsu Luncheon at Sheraton Palace Hotel in San Francisco